Pengolahan Air Limbah Betalaktam Menggunakan Reagen Kaporit, PAC, dan Alum Sulfat - Gede H. Cahyana; Gilang Gumilar; Tri Mulyani (Jurnal Serambi Engineering, 2021)
Beta lactam  antibiotics are pollutant in water bodies such as lakes and rivers. Beta lactam rings may have a negative impact on living beings  in lakes and rivers. Beta lactam rings also cause resistance or bacterial resistance to antibiotics. If human beings are  exposed to beta lactam ring, this  could negatively impact on their health. This study attempted  to break down the beta lactam rings  with several chemical reagents. These reagents hydrolyze the beta lactam ring and are then  analyzed using the  HPLC (High Performance Liquid Chromatography) instrument. This study aims to determine the how effective  the reagent for breaking the beta lactam ring. The research was conducted in  three stages: preliminary research, research on reagent effectiveness  , and research on β-lactamase degradation  using reagents. The results showed that calcium hypochlorite was able to  break the beta lactam cycle  with 100% efficiency.